Challenges in describing the conformation and dynamics of proteins with ambiguous behavior - Roca-Martinez, Joel; Lazar, Tamas; Gavalda-Garcia, Jose; Bickel, David; Pancsa, Rita; Dixit, Bhawna; Tzavella, Konstantina; Ramasamy, Pathmanaban; Sanchez-Fornaris, Maite; Grau, Isel; Vranken, Wim F. (Frontiers in Molecular Biosciences, 2022)
Traditionally, our understanding of how proteins operate and how evolution shapes them is based on two main data sources: the overall protein fold and the protein amino acid sequence. However, a significant part of the proteome shows highly dynamic and/or structurally ambiguous behavior, which cannot be correctly represented by the traditional fixed set of static coordinates. Representing such protein behaviors remains challenging and necessarily involves a complex interpretation of conformational states, including probabilistic descriptions. Relating protein dynamics and multiple conformations to their function as well as their physiological context (e.g., post-translational modifications and subcellular localization), therefore, remains elusive for much of the proteome, with studies to investigate the effect of protein dynamics relying heavily on computational models. We here investigate the possibility of delineating three classes of protein conformational behavior: order, disorder, and ambiguity. These definitions are explored based on three different datasets, using interpretable machine learning from a set of features, from AlphaFold2 to sequence-based predictions, to understand the overlap and differences between these datasets. This forms the basis for a discussion on the current limitations in describing the behavior of dynamic and ambiguous proteins.